Plan de mantenimiento preventivo para los transportadores de rodillos de la sección de empaque NPK en la empresa Yara Colombia S.A. ubicada en la zona industrial de Mamonal en Cartagena de Indias (2021)
This text reports on the problems of roller conveyor systems in the company Yara Colombia S.A. and the development of a maintenance plan. In the first part, to know the details of the main problem that statistically affects the systems, presenting considerable losses of approximately 162.6 tons per week. This is due to failures in the conveyors and in the mechanisms of the rollers, which are being affected by the chemical conditions of the transported product, which is highly corrosive and abrasive which causes them to be damaged and therefore the equipment cut off